2005
DOI: 10.1111/j.1469-8137.2005.01509.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursery pollination by a moth in Silene latifolia: the role of odours in eliciting antennal and behavioural responses

Abstract: Summary• Since the 1970s it has been known that the nursery pollinator Hadena bicruris is attracted to the flowers of its most important host plant, Silene latifolia , by their scent. Here we identified important compounds for attraction of this noctuid moth.• Gas chromatographic and electroantennographic methods were used to detect compounds eliciting signals in the antennae of the moth. Electrophysiologically active compounds were tested in wind-tunnel bioassays to foraging naïve moths, and the attractivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
150
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(161 citation statements)
references
References 65 publications
9
150
0
2
Order By: Relevance
“…In Silene latifolia, for example, the pollinating moth Hadena bicruris responds most strongly to lilac aldehydes (Dötterl et al, 2006), despite the presence of more than 40 volatiles in the total bouquet (Jürgens et al, 2002); these lilac aldehydes alone were able to replicate the behavioral effects of the full floral bouquet where other bouquet components were not. In work with S. latifolia and the closely related S. dioica, manipulating the emission of one key volatile, phenylacetaldehyde, had significant effects on pollen transfer; when the two species had similar levels of phenylacetaldehyde, interspecific transmission of pollen increased (Waelti et al, 2008).…”
Section: Research Articlementioning
confidence: 93%
“…In Silene latifolia, for example, the pollinating moth Hadena bicruris responds most strongly to lilac aldehydes (Dötterl et al, 2006), despite the presence of more than 40 volatiles in the total bouquet (Jürgens et al, 2002); these lilac aldehydes alone were able to replicate the behavioral effects of the full floral bouquet where other bouquet components were not. In work with S. latifolia and the closely related S. dioica, manipulating the emission of one key volatile, phenylacetaldehyde, had significant effects on pollen transfer; when the two species had similar levels of phenylacetaldehyde, interspecific transmission of pollen increased (Waelti et al, 2008).…”
Section: Research Articlementioning
confidence: 93%
“…The majority of variation in odor between the bouquets of the flowers from the two continents is attributed to veratrole emission, which is frequently absent in the scent bouquet of North American white campion . Although veratrole is a potent attractant to H. bicruris (Dötterl et al, 2006), this specialist pollinator did not accompany white campion to North America (Wolfe, 2002). In this population, the flower visitors are typically generalist insect pollinators (Young, 2002); thus, selection pressure on veratrole synthesis is presumably absent, contrary to European white campion, whose reproductive success apparently depends on the emission of this floral volatile (Dötterl et al, 2006).…”
Section: The Evolution Of Veratrole Emissionmentioning
confidence: 99%
“…Among the volatiles emitted by the male and female flowers of white campion is veratrole (1,2-dimethoxybenzene). Veratrole is one of only seven compounds emitted by white campion that elicit strong behavioral responses in H. bicruris (Dötterl et al, 2006). Following pollination, the emission of veratrole drastically decreases while the emission of other behaviorally active compounds remains unchanged (Muhlemann et al, 2006).…”
mentioning
confidence: 99%
“…Bioassays with pure compounds further confirmed that preference for mutant flowers resulted from an attraction to linalool and from the lack of defensive volatiles and stored products (linalool oxides). It has been shown that lilac compounds are important in a specialized nursery pollination system for recognition by the noctuid moth nursery pollinator of white campion (Silene latifolia) (Dötterl et al, 2006b(Dötterl et al, , 2007. Moreover, lilac aldehydes from Asimitellaria were shown to induce the nectaring behavior of long-tongued fungus gnats but are repellent for short-tongued fungus gnats in olfactometer tests (Okamoto et al, 2015).…”
Section: Cyp76c1 Influences the Interactions Of Flowers With Insectsmentioning
confidence: 99%